Urgensi Pengarusutamaan Moderasi Beragama melalui Aktualisasi Doktrin Aswaja An-Nahdliyah di Sekolah - Fahmi, Muhammad; Prasetia, Senata Adi; Rouf, Abd.; Syaifuddin, Syaifuddin; Djazilan, Sukron; Alfarizi, Muhammad Salman; Ma'mun, Adam Sukron (Proceedings of Annual Conference for Muslim Scholars, 2022)
The challenge in the life of religious people today is the extremism movement. Extremism is part of the form of a transnational movement that can have two pole dimensions, the left pole (secularism) and the right pole (textual-radicalism). In responding to this challenge, the religious moderation movement needs to be realized as a counter in dealing with it. This article explains the importance of mainstreaming religious moderation through aswaja an-nahdliyah education in schools in Indonesia. Through reading for text on relevant documents and content analysis, this article produces three substantive ideas. First, the mainstreaming of religious moderation needs to be realized in various fields and levels in every element of life, especially in educational institutions. Second, aswaja an-nahdliyah education (tawazun, tasamuh, tawasuth) contains teachings that are relevant to the substance of the policy and practice of religious moderation. Third, mainstreaming religious moderation can be realized through the practice of aswaja an-nahdliyah education in schools in Indonesia. Therefore, in order to equip the nation's children with the understanding and behavior of religious moderation, and prevent extremism movements, aswaja an-nahdliyah education needs to be made into the curriculum in every school in Indonesia.